USING THE FINNISH EDUCATIONAL EXPERIENCE IN THE DEVELOPMENT OF COGNITIVE ACTIVITY OF FUTURE TEACHERS BASED ON AN INNOVATIVE APPROACH - Yuldasheva Malohat Erkinovna (Galaxy International Interdisciplinary Research Journal, 2022)
Based on an innovative approach, this article discusses the specific benefits of using the Finnish educational experience in the development of the cognitive activity of future teachers, increasing the cognitive activity of young teachers, instilling in them a culture of self-confidence, independent work skills are described as an exemplary object of development